2019
DOI: 10.1111/cea.13454
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term high‐fat diet feeding protects from the development of experimental allergic asthma in mice

Abstract: Background A close association between obesity and asthma has been described. The nature of this association remains elusive, especially with respect to allergic asthma. Controversial findings exist regarding the impact of short‐term high‐fat diet (HFD) feeding on the development of allergic asthma. Objective To delineate the impact of short‐term HFD feeding on the development of experimental allergic asthma. Methods Female C57BL/6JRJ mice were fed with a short‐term HFD or chow diet (CD) for 12 weeks. Allergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…The authors suggested that this is an effect related to the short‐term of the diet and not to the obesogenic phenotype per se. The authors reported that HFD female mice presented a reduced airway hyperresponsiveness, airway inflammation, diminished Th1/TH17 but unchanged TH2 differentiation . These results are in line with our observations, where females also presented an attenuated inflammatory response to OVA after an even shorter high‐fat diet of 8 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…The authors suggested that this is an effect related to the short‐term of the diet and not to the obesogenic phenotype per se. The authors reported that HFD female mice presented a reduced airway hyperresponsiveness, airway inflammation, diminished Th1/TH17 but unchanged TH2 differentiation . These results are in line with our observations, where females also presented an attenuated inflammatory response to OVA after an even shorter high‐fat diet of 8 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…A similar experiment in female mice showed that HFD reduced inflammation and AHR due to an impaired ability of pulmonary DCs to induce T h 1 and T h 17 responses 90 . Although lung mucus production was comparable to levels in control diet‐fed mice, there was no investigation of GI tissues and it is unclear whether an HFD‐induced increase in faecal Proteobacteria and decrease in Firmicutes may have impacted the GI mucous barrier 90 . Sex‐specific differences in HFD‐induced obesity and AAD are well documented, 211 and further research may elucidate the effect of microbiota on these differences.…”
Section: Dysbiosis Of Gut Microbiome In Diet‐related Immune Disordersmentioning
confidence: 86%
“…There is less evidence of interactions between dietary lipids, the microbiome and lung mucus barrier in healthy states. Although mice fed HFDs have altered GI microbiome composition and develop respiratory inflammation, histopathology and impaired lung function, they do not have altered lung mucus production without another stimulus such as in disease models 57,90,133 . More detailed analysis of mucus composition and characterization of the respiratory microbiome would provide further insights.…”
Section: Macronutrients: Impact On Microbiome and Mucous Barriermentioning
confidence: 99%
“…Schroder and colleagues examined the effect of short-term HFD, mild weight gain on the induction of the asthma phenotype in mice. 35 In these studies, the author show that female (C57BL6JRJ) mice feed HFD to induce mild increase in body weight accompa- The two studies clearly show that metainflammation can alter allergic disease susceptibility and severity and that further in-depth studies will be required to fully decipher the mechanism of action.…”
Section: Metainflammation and Asthmamentioning
confidence: 99%
“…Schroder and colleagues examined the effect of short‐term HFD, mild weight gain on the induction of the asthma phenotype in mice 35 . In these studies, the author show that female (C57BL6JRJ) mice feed HFD to induce mild increase in body weight accompanied by mild metabolic alterations develop a less severe asthma phenotype.…”
Section: Experimental Models Of Allergic Diseasementioning
confidence: 99%